M-Learning: An Integrative Approach to Increase Student Engagement - Vargas Barquero, Vivian (2020)
M-learning utilizes handheld electronic devices as didactic tools for facilitating learning and teaching within real-time access in the language classroom. Current studies on m-learning suggest that the incorporation of electronic devices can lead to greater student engagement and better performance. Using a questionnaire, 22 professors from the major Bachelor’s in the Teaching of English as a Foreign Language from the Universidad Nacional (Costa Rica) were surveyed about how mobile devices are being implemented in the language classroom.